HAMBATAN WARGA BELAJAR KEAKSARAAN FUNGSIONAL (KF) DALAM MENGIKUTI KEGIATAN PEMBELAJARAN DI SKB 2 TANAH DATAR - Fauzia Panca Sukma dan MHD Natsir (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2014)
The research is background by the declining presence of people learning keaksaraan fungsional (KF) KF in participating in learning activities in Tanah Datar SKB 2 is characterized KF activity and lack of seriousness in following learning activities participants KF. This study aims to look at the barriers people learning to follow the activities of studyed KF in terms of health, time, location and facilities. This research is descriptive quantitative . The population in this study were all residents of functional literacy learning as many as 40 people, as well as sample the data analysis techniques using a percentage formula . The results showed that : (1) the learners have problems in terms of health. (2) the learners have problems in terms of time. (3) the learners have problems in terms of location. (4) the learners have problems in terms of facilities.